Tinjauan Atas Strategi E-Marketing Pada Kinasih Resort & Conference Bogor - Noor, Tubagus Dicky Faldy Syahid; Nurvenda, Siti Suryani (Prodi Pariwisata dan LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
E-Marketing is an effort to market products and services using online platforms via the internet. The use of E-Marketing can reach a wider audience than traditional media and is more cost effective in marketing. E-Marketing opens up new opportunities to improve marketing strategies to achieve better results. With the help of E-marketing, companies can implement more practical strategies because potential customers can easily get information about products and services and do business via the Internet. The purpose of this review is to find out: 1) To find out what forms of E-Marketing are implemented at the Kinasih Resort & Conference Bogor; 2) To find out what E-Marketing strategies are implemented at Kinasih Resort & Conference Bogor; 3) What are the obstacles and how to overcome obstacles in implementing the EMarketing strategy at Kinasih Resort & Conference.The results of this review are: 1) Kinasih Resort & Conference Bogor has implemented four types of E-marketing; 2) Kinasih Resort & Conference Bogor has implemented seven E-marketing strategies; 3) In its implementation, there are several obstacles experienced by Kinasih Resort & Conference Bogor, including a lack of human resources in the digital marketing division, a lack of interesting and aesthetic content, and less responsive sales. The efforts made by Kinasih Resort & Conference Bogor to overcome obstacles include making additions and improvements in the field of human resources (HR) for the Digital Marketing division, and increasing the number of variations of interesting and aesthetic content on social media. Keywords: E-Marketing, Kinasih Resort & Conference Bogor